Phosphodiesterase 10A inhibition attenuates sleep deprivation-induced deficits in long-term fear memory. (2nd December 2016) - Guo, Lengqiu; Guo, Zhuangli; Luo, Xiaoqing; Liang, Rui; Yang, Shui; Ren, Haigang; Wang, Guanghui; Zhen, Xuechu
Highlights: MP-10 ameliorates sleep deprivation-induced long term fear memory deficit. REM-SD causes decline of pCREB and BDNF in hippocampus and striatum. Recovery of pCREB and BDNF levels by MP-10 benefits long term fear memory. Abstract: Sleep, particularly rapid eye movement (REM) sleep, is implicated in the consolidation of emotional memories. In the present study, we investigated the protective effects of a phosphodiesterase 10A (PDE10A) inhibitor MP-10 on deficits in long-term fear memory induced by REM sleep deprivation (REM-SD). REM-SD caused deficits in long-term fear memory, however, MP-10 administration ameliorated the deleterious effects of REM-SD on long term fear memory. Brain-derived neurotropic factor (BDNF) and phosphorylated cAMP response element-binding protein (pCREB) were altered in specific brain regions associated with learning and memory in REM-SD rats. Accordingly, REM-SD caused a significant decrease of pCREB in hippocampus and striatum and a significant decrease of BDNF in the hippocampus, striatum and amygdala, however, MP-10 reversed the effects of REM-SD in a dose-dependent manner. Our findings suggest that REM-SD disrupts the consolidation of long-term fear memory and that administration of MP-10 protects the REM-SD-induced deficits in fear memory, which may be due to the MP-10-induced expression of BDNF in the hippocampus, striatum and amygdala, and phosphorylation of CREB in the hippocampus and striatum.